Predicting the distribution of Australian frogs and their overlap with Batrachochytrium dendrobatidis under climate change. (3rd May 2022) - Sopniewski, Jarrod; Scheele, Benjamin C.; Cardillo, Marcel
Abstract: Aim: Amphibians, with over 40% of assessed species listed as threatened, are disproportionately at risk in the global extinction crisis. Among the many factors implicated in the ongoing loss of amphibian biodiversity are climate change and the disease chytridiomycosis, caused by the fungus Batrachochytrium dendrobatidis ( Bd ). These threats are of particular concern in Australia, where Bd has been implicated in the declines of at least 43 frog species, and climate change is emerging as an additional threat. We explore how climate change is likely to affect the distributions of Australian frog species and Bd to the year 2100, and how the spatial and climatic niche overlap between chytridiomycosis‐declined frogs and Bd could shift. Location: Australia. Methods: We used species distribution modelling to infer the current and future distribution of 141 Australian frog species and Bd, under two emissions scenarios. We used various metrics of niche similarity to quantify predicted alterations to spatial interactions between Bd and frog species. Results: Climate change is likely to have a variable impact on frog distributions in Australia, with some 23 and 47 species, primarily in southern Australia, predicted to lose at least 30% of their current distributions under low and high emissions scenarios, respectively. In contrast, 69 and 68 species, respectively, have potential to increase their distributions, primarily in northern Australia. While the distribution of Bd is predicted to decrease, the proportional spatial and niche overlap between Bd and susceptible frog species is predicted to remain little changed, and in some cases, to increase. Main conclusions: Although effects will be variable across the continent, climate change is likely to be a threatening factor to many Australian frog species. Additionally, chytridiomycosis is likely to remain a significant threat to many frog species, as any reductions to the pathogen's distribution largely coincide with geographic range contractions of chytridiomycosis‐susceptible species.